Two new species of the genus Sinonychus (Coleoptera, Elmidae) from Guizhou, China - Ri-Xin Jiang; Xiang-Sheng Chen (ZooKeys)
The riffle beetle genus Sinonychus Jäch & Boukal, 1995 (Elminae, Macronychini) includes only three species from East Asia. In this paper, two new species, S. lipinae sp. nov. and S. luodianensis sp. nov., are described from Guizhou Province, China. Illustrations of the new species and a key to all five Sinonychus species are also provided.